Second-harmonic generation tuning by stretching arrays of GaAs nanowires. Issue 24 (13th June 2022) - Saerens, Grégoire; Bloch, Esther; Frizyuk, Kristina; Sergaeva, Olga; Vogler-Neuling, Viola V.; Semenova, Elizaveta; Lebedkina, Elizaveta; Petrov, Mihail; Grange, Rachel; Timofeeva, Maria
Abstract : We present a wearable device with III–V nanowires in a flexible polymer, which is used for active mechanical tuning of the second-harmonic generation intensity. Abstract : We present a wearable device with III–V nanowires in a flexible polymer, which is used for active mechanical tuning of the second-harmonic generation intensity. An array of vertical GaAs nanowires was grown with metalorganic vapour-phase epitaxy, then embedded in polydimethylsiloxane and detached from the rigid substrate with mechanical peel off. Experimental results show a tunability of the second-harmonic generation intensity by a factor of two for 30% stretching which matches the simulations including the distribution of sizes. We studied the impact of different parameters on the band dispersion and tunability of the second-harmonic generation, such as the pitch, the length, and the diameter. We predict at least three orders of magnitude active mechanical tuning of the nonlinear signal intensity for nanowire arrays. The flexibility of the array together with the resonant wavelength engineering make such structures perspective platforms for future bendable or stretchable nanophotonic devices as light sources or sensors.